Soothing the heart with music: A feasibility study of a bedside music therapy intervention for critically ill patients in an urban hospital setting. Issue 1 (February 2020) - Fallek, Ronit; Corey, Kristen; Qamar, Aamna; Vernisie, Shawna N.; Hoberman, Alexander; Selwyn, Peter A.; Fausto, James A.; Marcus, Paula; Kvetan, Vladimir; Lounsbury, David W.
Abstract: Objectives: Music therapy has been shown to be effective for reducing anxiety and pain in people with a serious illness. Few studies have investigated the feasibility of integrating music therapy into general inpatient care of the seriously ill, including the care of diverse, multiethnic patients. This leaves a deficit in knowledge for intervention planning. This study investigated the feasibility and effectiveness of introducing music therapy for patients on 4 inpatient units in a large urban medical center. Capacitated and incapacitated patients on palliative care, transplantation, medical intensive care, and general medicine units received a single bedside session led by a music therapist. Methods: A mixed-methods, pre-post design was used to assess clinical indicators and the acceptability and feasibility of the intervention. Multiple regression modeling was used to evaluate the effect of music therapy on anxiety, pain, pulse, and respiratory rate. Process evaluation data and qualitative analysis of observational data recorded by the music therapists were used to assess the feasibility of providing music therapy on the units and patients' interest, receptivity, and satisfaction. Results: Music therapy was delivered to 150 patients over a 6-month period. Controlling for gender, age, and session length, regression modeling showed that patients reported reduced anxiety post-session. Music therapy was found to be an accessible and adaptable intervention, with patients expressing high interest, receptivity, and satisfaction. Significance of Results: This study found it feasible and effective to introduce bedside music therapy for seriously ill patients in a large urban medical center. Lessons learned and recommendations for future investigation are discussed.